2012
DOI: 10.1080/13548506.2012.658819
|View full text |Cite
|
Sign up to set email alerts
|

Starting on haemodialysis: A qualitative study to explore the experience and needs of incident patients

Abstract: Dialysis can be very stressful with the initial months onto treatment being highly critical in terms of both adaptation and mortality. This qualitative study aimed to explore the lived experiences of incident haemodialysis patients in Singapore. Topics related to the end-stage renal disease diagnosis and haemodialysis treatment were raised with 13 incident haemodialysis patients in the form of semi-structured interviews, and interpretative phenomenological analysis was undertaken as the framework for data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 33 publications
3
71
1
Order By: Relevance
“…Participants expressed frustration, because dialysis required relocation or reduced the time and energy available to care for family members or carry out family duties (27)(28)(29)35). Some participants were now dependent on family for care or assistance and worried that they had become a burden to them (28)(29)(30)37,38). Participants who thought their dialysis dependence had restricted their families' activities, such as holidays, also reported guilt (29,30,35).…”
Section: Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Participants expressed frustration, because dialysis required relocation or reduced the time and energy available to care for family members or carry out family duties (27)(28)(29)35). Some participants were now dependent on family for care or assistance and worried that they had become a burden to them (28)(29)(30)37,38). Participants who thought their dialysis dependence had restricted their families' activities, such as holidays, also reported guilt (29,30,35).…”
Section: Synthesismentioning
confidence: 99%
“…When dialysis commenced, participants reported that they lost ambitions for the future, such as traveling and enjoying retirement (28,29,37,39). With dependence on dialysis, they were confronted with their own mortality (28-32,35,37,39), and this could be reinforced by the deaths of other patients in the dialysis unit (30,31,39).…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations